Effects of Different Purification Methods on Chicken Feather Keratin - Pourjavaheri, Firoozeh; Mohaddes, Farzad; Shanks, Robert A.; Czajka, Michael; Gupta, Arun (Trans Tech Publications, Switzerland, 2014)
Every year billion kilograms of unused feathers result from the poultry industry worldwide, which in effect impose a difficult disposal process to the environment. Chicken feathers are considered as a valuable and renewable keratin protein source, which could be used advantageously in a number of applications as alternatives to feather meal and feather disposal. Although the potential applications of keratin derived from chicken feathers have been investigated, the initial purification phase has not been fully described in the literature. Original chicken feathers contain many biological organisms along with other contaminants after plucking. Unprocessed chicken feathers are considered as potentially hazardous biological materials due to the presence of blood borne pathogens; therefore,the decontamination process is very important. The purpose of this work is to compare the effects of different purification techniques on chicken feathers prior to keratin isolation. These processes include surfactant washing, soxhlet extraction with ethanol, ozone, and sodium chlorite solutions. Thermogravimetric analysis, vibrational spectroscopy, and wide angle X-ray scattering were used to characterise the purified feathers prior to keratin extraction.